Tuberculosis: challenges to improve the treatment - Santos, Jean Leandro dos [UNESP]; Lima, Mariana Moreira [UNESP]; Trindade, Ariane Biolcati [UNESP]; Carnavalli, Flávia [UNESP]; Melchior, Aylime Castanho Bolognesi [UNESP]; Chin, Chung Man [UNESP] (Bentham Science Publishers, 2013)
Tuberculosis is one of the leading causes of morbidity and mortality worldwide. Current treatment has several challenges including multi-drug resistance, extensively drug-resistance and HIV co-infection. Problems related to patients, treatment and health care system also contributes negatively to this panel. This review summarizes the main obstacles to treat tuberculosis and discuss several strategies to improve the treatment.
Keywords: Epigenetics; Histone; IVF; Embryo cryopreservation; Bovine